Feeling the heat : dispatches from the front lines of climate change - Motavalli, Jim; Deneen, Sally (Routledge, 2004)
This book consists of chapter-length visits to world "hot" spots, where people are already coping with the consequences of climactic disruption. It reveals the process of climate change to be ongoing, serious and immediate